Strategies for smart and sustainable transport from a gender perspective - González-Sánchez, Guadalupe; Maeso-González, Elvira; Olmo-Sánchez, María Isabel (My University, 2022)
Mobility, and especially urban mobility, has changed drastically in recent times. This has been due, on the one hand, to the development and application of new technologies that have led to new modes of transport, fuels and resource sharing. On the other hand, the impact on mobility and logistics of the COVID-19 pandemic crisis, which has led to a decrease in the number of daily trips, changes in the choice and use of transport modes and the accelerated evolution of B2C e-commerce logistics distribution. Gender differences in mobility patterns are well known. Although the geographical, social and cultural context may influence mobility habits, and may make these gender differences more or less pronounced, the literature published over the years has identified common patterns or trends in developed countries. On the other hand, the effects of the COVID-19 crisis in the social and economic sphere have aggravated inequalities between population groups, with women being one of the most affected groups, which may accentuate this gender gap in mobility. Mobility and transport policies should aim at an efficient and sustainable use of transport modes, while ensuring road safety and equal opportunities of use. Through a strategic analysis of urban mobility from a gender perspective, strategies are identified and recommendations are offered for policy decisions in mobility planning towards smarter urban mobility.
Keywords: Movilidad residencial; Efectos de la COVID 19; Transporte - Innovaciones tecnológicas; Sexismo; Mobility; Gender; Technology; Strategy